Contribution of low- and high-flux capillaries to slow hemodynamic fluctuations in the cerebral cortex of mice. Issue 8 (August 2016) - Li, Baoqiang; Lee, Jonghwan; Boas, David A; Lesage, Frederic
We employed optical coherence tomography to measure cerebral cortical capillary red blood cell (RBC) flux in mice. The results suggest that baseline-flux weakly depends on cortical depth. Furthermore, under hypercapnia, low baseline-flux capillaries exhibit greater flux increases while the higher ones saturate, resulting in RBC-flux homogenization. Power-spectrum analysis indicates that higher flux capillaries saw greater flux variability in the low-frequency range (0.01–0.1 Hz) both at baseline and during hypercapnia. These results suggest that lower baseline-flux capillaries have more reserve to deliver oxygen with increased blood flow; but higher ones more strongly impact the low-frequency fluctuations associated with BOLD fMRI measurements of resting state functional connectivity.